1950
DOI: 10.1104/pp.25.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Nutrition of Alfalfa

Abstract: Molybdenum is the latest element to be found essential for microorganisms and higher plants. The literature, recently reviewed by MULDER (12), indicates that Mo is necessary for N fixation by Azotobacter and Rhizobium and for the metabolism of nitrates by all plants. The biological importance of Mo was originally discovered by BORTELS (3, 4), who reported that Azotobacter and peas, soybeans, and red clover showed increases in growth and in N fixation from additions of Mo. Essentiality of Mo for higher plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1951
1951
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…With reference to other possible functions of molybdenum, Hewitt & Agar wala (63) report that a molybdenum deficiency in representative higher plants greatly depresses the reduction of triphenyltetrazolium by the tissues. This is in line with the results previously reported by Evans et al (43) that homogenates of molybdenum-deficient lucerne foliage had a decreased hydrogenase activity as measured by methylene blue reduction. The signifi cance of metal deficiency effect on enzyme activity such as reported above, is discussed in the section, "Metal Deficiencies and Enzyme Constitution."…”
Section: Enzymesupporting
confidence: 93%
“…With reference to other possible functions of molybdenum, Hewitt & Agar wala (63) report that a molybdenum deficiency in representative higher plants greatly depresses the reduction of triphenyltetrazolium by the tissues. This is in line with the results previously reported by Evans et al (43) that homogenates of molybdenum-deficient lucerne foliage had a decreased hydrogenase activity as measured by methylene blue reduction. The signifi cance of metal deficiency effect on enzyme activity such as reported above, is discussed in the section, "Metal Deficiencies and Enzyme Constitution."…”
Section: Enzymesupporting
confidence: 93%
“…Garner and Allard (3) have shown that short alternations of light and dark inhibit the growth of many plants. Arthur, Guthrie, and Newell (1) found that tomato plants were extremely sensitive to long day length and will not survive under continuous illumination. The leaf injury symptoms reported by these authors are similar to those observed here-small, stiff, yellow leaves with dark necrotic spots.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that molybdenum is necessary for the utilization of nitrates by legumes (1,6) and that an increased supply is required when leguminous plants are forced to utilize atmospheric nitrogen. Jensen (4) has reported that nodules from alfalfa contain 5 to 15 times higher concentrations of molybdenum than roots of plants.…”
mentioning
confidence: 99%
“…The purified protein was subjected to metal content analysis using inductively coupled plasma-mass spectrometry ([ICP-MS] SPQ-9000 with SII nanotechnology) after wet-sample digestion by 5 ml of HNO 3 and 1 ml of HClO 4 (11). Controls were conducted using [2Fe-2S]-ferredoxin from spinach (Sigma) and bovine serum albumin (Sigma).…”
Section: Methodsmentioning
confidence: 99%